Positive electrode material and preparation method thereof, lithium ion battery and electric device

By introducing specific doping elements and multi-stage sintering processes into the positive electrode materials of lithium-ion batteries, a positive electrode material with high energy density and long cycle life is prepared, which solves the reduction in the cycle retention rate of existing materials when increasing the voltage and Ni content. question.

CN119481031APending Publication Date: 2025-02-18BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411899523.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The current lithium-ion battery positive electrode materials will reduce the cycle retention rate when increasing the voltage and Ni content, making it difficult to meet the market's demand for high energy density and long cycle life.

Method used

A positive electrode material including a specific compound is proposed, with the chemical formula of LiaNibCocMndMeO2, and M includes Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo , at least one element of Y, Sn, V, Cu, Ag, and Zn, and the lattice distortion change rate is within the range of 1%≤△J50≤20%, and 2%≤△J100≤40%. The material is prepared by a multi-stage sintering process, introducing doping and coating elements to improve structural stability and cycling performance.

Benefits of technology

The cathode material used at high voltage has a long cycle life and high energy density, meeting the market's high performance demand for lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005203511010000151
    Figure BDA0005203511010000151
  • Figure BDA0005203511010000161
    Figure BDA0005203511010000161
  • Figure BDA0005203511010000162
    Figure BDA0005203511010000162
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a positive electrode material, a preparation method thereof and a power utilization device, the positive electrode material comprises a compound shown in the formula I: LiaNibCocMndMeO2, the lattice distortion change rate of the positive electrode material is that J50 is larger than or equal to 1% and smaller than or equal to 20%, and J100 is larger than or equal to 2% and smaller than or equal to 40%; wherein J50 is equal to (J50-J0) / J0, J100 is equal to (J100-J0) / J0, and J0, J50 and J100 are lattice distortion of the positive electrode material when the charging states of the battery adopting the positive electrode material are 0% SOC, 50% SOC and 100% SOC respectively. The positive electrode material is good in structural stability and high in capacity, and the battery adopting the positive electrode material can have relatively high energy density and relatively long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to positive electrode materials and preparation methods thereof, lithium-ion batteries and electrical devices. Background Art

[0002] Lithium-ion battery is a green secondary battery with outstanding advantages such as high voltage, high energy density, good cycle performance, low self-discharge and no memory effect. Since its successful development in the 1990s, it has been rapidly applied and developed. In recent years, the application scope of lithium-ion batteries has become more and more extensive, including energy storage power supply systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.

[0003] The cathode material is the most expensive part of lithium-ion batteries, and its performance also plays a decisive role in lithium-ion batteries. Therefore, the market has put forward requirements for lithium-ion batteries with higher energy density and longer cycle life. At present, the main methods to solve the energy density problem are to increase the operating voltage, increase the Ni content of the material, and high compaction. However, the cycle retention rate of the cathode materials currently used in the market will decrease when the voltage is increased and the Ni content is increased. Therefore, there is an urgent need for lithium-ion battery cathode materials with high energy density and long cycle life. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the present invention provides a positive electrode material that can be used at high voltage and has a long cycle life, a preparation method thereof, a lithium ion battery and an electric device.

[0005] In a first aspect of the present application, a positive electrode material is provided. According to an embodiment of the present application, the positive electrode material comprises a compound shown in formula I:

[0006] Li a Ni b Co c Mn d M e O2 Formula I

[0007] In formula I, 0.8≤a≤1.2, 0<b<1, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.4;

[0008] M includes at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn;

[0009] The lattice distortion change rate of the positive electrode material satisfies: 1%≤△J 50 ≤20%, 2%≤△J100 ≤40%;

[0010] Among them, △J 50 =(J 50 -J0) / J0,△J 100 =(J 100 -J0) / J0, J0, J 50 , J 100 The lattice distortion of the positive electrode material when the charging states of the battery using the positive electrode material are 0% SOC, 50% SOC and 100% SOC respectively.

[0011] In some embodiments, 1%≤ΔJ 50 ≤10%, 2%≤△J 100 ≤20%.

[0012] According to the positive electrode material of the embodiment of the present application, the lattice distortion change rate meets the above conditions, indicating that the lattice distortion of the positive electrode material during the battery charging and discharging process is small, the stability of the crystal structure is good, and it can meet the use requirements under high voltage conditions, and thus has a higher energy density and a longer cycle life.

[0013] According to an embodiment of the present application, in the above formula I, M includes at least one element selected from Ti, Zr, Nb, W, Al, Mg, and Sr. This helps to improve the structural stability of the positive electrode material, thereby improving the energy density and cycle life of the lithium-ion battery using the positive electrode material.

[0014] According to an embodiment of the present application, the D of the positive electrode material 50 Particle size change rate △D 50 Satisfy: 10% ≤ △D 50 ≤60%. In some specific embodiments, the D 50 Particle size change rate △D 50 Satisfy: 10% ≤ △D 50 ≤40%.

[0015] Specifically, D 50 Particle size change rate △D 50 It can reflect the bulk particle strength of the positive electrode material, △D 50 The larger the value, the weaker the strength of the positive electrode material particles. 50 Meeting the above range indicates that the positive electrode material has better particle strength, higher structural stability, and the particles are not easy to break, which is beneficial to improving the cycle life of the positive electrode material.

[0016] According to an embodiment of the present application, the specific surface area increase rate ΔSSA of the positive electrode material satisfies: 10%≤ΔSSA≤80%. In some specific embodiments, the specific surface area increase rate ΔSSA of the positive electrode material satisfies: 10%≤ΔSSA≤50%.

[0017] Specifically, the specific surface area increase rate △SSA of the positive electrode material can reflect the bulk anti-powdering degree of the positive electrode material. The larger the △SSA, the easier the positive electrode material is to be powdered. If the △SSA satisfies the above range, it indicates that the positive electrode material is not easy to be powdered and has high stability, which is beneficial to improve the energy density and cycle life of the positive electrode material.

[0018] In a second aspect of the present application, a method for preparing the positive electrode material described above is provided. According to an embodiment of the present application, the method comprises: 1 The first intermediate is obtained by first mixing the compound of the element, and the first mixture is first sintered at T1 = 850 ° C ~ 1000 ° C to obtain a first intermediate; the first intermediate is mixed with the compound containing M 2 The second intermediate is obtained by mixing the compound of the element for the second time, and the second mixture is sintered for the second time at T2 = 600 ° C ~ 850 ° C to obtain a second intermediate; the second intermediate and the compound containing M 3 The compound of the element is mixed for the third time, and the obtained third mixture is sintered for the third time at T3 = 450 ° C ~ 650 ° C to obtain the positive electrode material; wherein, M 1 、M 2 、M 3 Each independently includes at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn.

[0019] According to the embodiments of the present application, 2 The amount of the compound containing M is greater than that of the compound containing M 1 The amount of the compound containing M 2 The amount of the compound containing M is greater than that of the compound containing M 3 Thus, M with a suitable amount of 1 Elements enter the crystal structure of the positive electrode material and will not be enriched at the grain boundary or surface. 2 Elements entering the shallow surface layer of the positive electrode material can effectively increase the capacity of the positive electrode material. 3 The elements can effectively cover the surface of the positive electrode material without affecting the conductivity of the positive electrode material.

[0020] According to the embodiments of the present application, the 1M in the compound of element 1 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 1 / (Ni+Co+Mn) satisfies 0 <M 1 / (Ni+Co+Mn)<0.1. Within the above content range, M 1 The element is easy to be uniformly doped into the cathode material, for example, it can enter the lattice of the cathode material. Combined with the reaction temperature in the first sintering step, M 1 The elements penetrate deeply into the positive electrode material, which can increase the high voltage tolerance performance of the positive electrode material while achieving higher capacity.

[0021] According to the embodiments of the present application, the 2 M in the compound of element 2 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 2 / (Ni+Co+Mn) satisfies 0 <M 2 / (Ni+Co+Mn)<0.2. Within the above content range, combined with the reaction temperature in the second sintering step, M 2 The elements enter the positive electrode material at a shallow depth and can be easily and evenly doped into the shallow surface layer of the positive electrode material. At the same time, they can melt and grow to effectively repair the defects on the surface of the positive electrode material, thereby increasing the cycle life of the positive electrode material.

[0022] According to the embodiments of the present application, the 3 M in the compound of element 3 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 3 / (Ni+Co+Mn) satisfies 0 <M 3 / (Ni+Co+Mn)<0.1. Within the above content range, combined with the reaction temperature in the third sintering step, M 3 The elements are mainly coated on the surface of the positive electrode material, which can reduce side reactions during the cycle and further reduce the gas production of the positive electrode material during the cycle.

[0023] According to an embodiment of the present application, the rotation speed R1 in the first mixing step may be 1500-2000 rpm. 1 The compound of the element is evenly distributed on the surface of the cathode material precursor and enters into the crystal structure of the first intermediate.

[0024] According to the embodiment of the present application, the first sintering time t1 may be 15 to 25 hours. Within the above time range, the reaction can be fully carried out without wasting too much time.

[0025] According to an embodiment of the present application, the rotation speed R2 in the second mixing step can be 1800-2300 rpm. 2 The compound of the element is evenly distributed on the surface of the first intermediate and enters into the crystal structure of the positive electrode material.

[0026] According to the embodiment of the present application, the second sintering time t2 can be 12 to 18 hours. Within the above time range, the reaction can be fully carried out without wasting too much time.

[0027] According to an embodiment of the present application, the rotation speed R3 in the third mixing step may be 1000-1600 rpm. 3 The compound of the element is evenly distributed on the surface of the first intermediate and enters into the crystal structure of the positive electrode material.

[0028] According to the embodiment of the present application, the time t3 of the third sintering can be 7 to 13 hours. Within the above time range, the reaction can be fully carried out without wasting too much time.

[0029] According to the embodiments of the present application, R2-R1=300-800; R2-R3=800-1300; R1-R3=200-800. Specifically, the first mixing is at an intermediate speed, mainly because the sintering temperature is the highest, and the additives are more easily evenly diffused into the material body. If the speed is too high, the additive dispersion reaction will be too strong, which will affect the amount of Li embedded and the capacity will be low, so the speed does not need to be the highest; the second mixing speed is the highest, mainly because the subsequent sintering temperature is in the middle section, and at the same time, it is hoped that the additives are the effect of surface interface doping, so the high speed makes the additives evenly distributed, which is conducive to the surface interface reaction of the material, can improve the stability of the material surface, resist the electrolyte side reaction, and improve the cycle performance; the third mixing speed is the lowest, because the reaction temperature of the subsequent sintering is low, and the additives are in a surface attachment state. If the additives are evenly distributed, it will affect the material ions entering the electrolyte, increase the impedance, and reduce the capacity. Therefore, it is necessary to achieve the effect of island distribution of additives, so the speed is the lowest. The speed difference at different stages can make the corresponding additives play the effects of bulk doping, surface doping and avoiding coating, and further improve the performance of the positive electrode material.

[0030] According to the embodiments of the present application, M 1 、M 2 、M 3 Each independently comprises at least one element of Ti, Zr, Nb, W, Al, Mg, and Sr. Thus, it is beneficial to improve the conductivity of the positive electrode material, improve ion diffusion, structural stability, capacity, and cycle stability, and further improve the energy density and cycle life of the lithium-ion battery using the positive electrode material.

[0031] In a third aspect of the present application, a lithium-ion battery is provided. According to an embodiment of the present application, the lithium-ion battery comprises the positive electrode material described above or the positive electrode material prepared by the method described above. The lithium-ion battery has a high energy density and a long cycle life.

[0032] The fourth aspect of the present application provides an electrical device, comprising the lithium-ion battery described in the third aspect of the present application. The electrical device has all the features and advantages of the lithium-ion battery described above, which will not be described one by one here. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 It is the charge and discharge cycle curve of Example 1 and Comparative Example 1 of the present application.

[0034] Figure 2 This is a SEM photograph of the positive electrode material before pressing in Example 1 of the present application.

[0035] Figure 3 This is a SEM photograph of the positive electrode material after compression in Example 1 of the present application.

[0036] Figure 4 This is a SEM photograph of the positive electrode material in Comparative Example 1 of the present application before compression.

[0037] Figure 5 This is a SEM photograph of the positive electrode material after compression in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0038] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0039] During the charging process of lithium-ion batteries, lithium ions are removed from the positive electrode material. This process is accompanied by changes in the lattice parameters, because the removal of lithium ions causes vacancies in the lattice. As charging progresses, the valence of the transition metal ions in the positive electrode material may increase, which will cause more vacancies and stress in the lattice, thereby causing lattice distortion. During the discharge process, lithium ions are re-embedded into the positive electrode material. This process requires the lattice to accommodate lithium ions, and the lattice parameters will also change accordingly. Long-term charge and discharge cycles may cause excessive lattice distortion, continuous accumulation of stress, and structural degradation, such as lattice cracking, particle crushing, and shedding of the surface layer, which will affect the cycle life and safety of the battery. If the lattice distortion is reduced, the stability of the positive electrode material can be improved, thereby extending the service life of the battery.

[0040] In view of this, the first aspect of the present application provides a positive electrode material. According to an embodiment of the present application, the positive electrode material includes a compound shown in formula I:

[0041] Li a Ni b Co c Mn d M e O2 Formula I

[0042] In formula I, 0.8≤a≤1.2, 0<b<1, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.4;

[0043] M includes at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn;

[0044] The lattice distortion change rate of the positive electrode material satisfies: 1%≤△J 50 ≤20%, 2%≤△J 100 ≤40%;

[0045] Among them, △J 50 =(J 50 -J0) / J0,△J 100 =(J 100 -J0) / J0, J0, J 50 , J 100 The lattice distortion of the positive electrode material when the charging states of the battery using the positive electrode material are 0% SOC, 50% SOC and 100% SOC respectively.

[0046] In order to test the lattice distortion of the positive electrode material at 0% SOC, 50% SOC, and 100% SOC, the present application prepares the positive electrode material into a slurry, applies it to the positive electrode current collector to form a positive electrode sheet, and assembles the positive electrode sheet, negative electrode sheet, isolation membrane, and electrolyte into a battery. Before the positive electrode active material is assembled into the battery, the J0 of the positive electrode active material is obtained by testing with an X-ray diffractometer; or the battery is assembled to an initial state of 0% SOC, or the battery is discharged to 0% SOC, the battery is disassembled, the positive electrode material on the positive electrode sheet is scraped off, and the J0 of the positive electrode material is obtained by testing with an X-ray diffractometer; after the battery is charged to 50% SOC and 100% SOC respectively, the battery is disassembled, the positive electrode material on the positive electrode sheet is scraped off, and the J of the positive electrode active material is tested with an X-ray diffractometer under the same test conditions. 50 , J 100 .

[0047] As an example, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer located on the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material, a binder and a conductive agent provided in the first aspect of the present application.

[0048] As an example, the type and content of the binder are not particularly limited, and the binder may include one or more of polyvinylidene fluoride (PVDF), vinylidene fluoride copolymers, or modified derivatives thereof (eg, carboxylic acid, acrylic acid, acrylonitrile, etc. modified).

[0049] As an example, the type and content of the conductive agent are not particularly limited, and the conductive agent may include one or more of acetylene black, conductive carbon black, carbon fiber (VGCF), carbon nanotube (CNT), and Ketjen black.

[0050] As an example, the positive electrode current collector can generally be a layer body, and the positive electrode current collector is generally a structure or part that can collect current. The positive electrode current collector can be various materials in the art that are suitable for use as a positive electrode current collector for an electrochemical energy storage device. For example, the positive electrode current collector can be including but not limited to metal foil, and more specifically can be including but not limited to nickel foil and aluminum foil.

[0051] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located on the surface of the negative electrode current collector, and the negative electrode active material layer generally includes a negative electrode active material. The negative electrode active material is a conventional choice in the battery field, and the type and content are not specifically limited, and can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate, or other metals that can form alloys with lithium.

[0052] Among them, the graphite may include one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material may include one or more of elemental tin, tin oxide compounds, and tin alloys.

[0053] The negative electrode current collector is generally a structure or part that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for lithium secondary batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, more specifically can include but is not limited to copper foil. In addition, the negative electrode plate can also be a lithium plate.

[0054] As an example, the isolation membrane is a common choice in the battery field. The type and content are not specifically limited and can be one or more of polyethylene, polypropylene, polyvinylidene fluoride, aramid, polyethylene terephthalate, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyamide, polyester and natural fibers.

[0055] As an example, the electrolyte is a conventional choice in the battery field, and its type and content are not specifically limited. It can be various electrolytes suitable for lithium secondary batteries in the field. For example, the electrolyte generally includes an electrolyte and a solvent. The electrolyte generally may include a lithium salt. More specifically, the lithium salt may be an inorganic lithium salt and / or an organic lithium salt, specifically including but not limited to one or more of LiPF6, LiBF4, LiN(SO2F)2 (abbreviated as LiFSI), LiN(CF3SO2)2 (abbreviated as LiTFSI), LiClO4, LiAsF6, LiB(C2O4)2 (abbreviated as LiBOB), and LiBF2C2O4 (abbreviated as LiDFOB).

[0056] In some embodiments, 1%≤ΔJ 50 ≤10%, 2%≤△J 100 ≤20%. As an example, △J 50 Specifically, it can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, etc.; △ J 100 Specifically, it can be 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, 40% and the like.

[0057] In this article, the term "lattice distortion" refers to the phenomenon that the position of atoms or ions in the positive electrode material crystal changes, resulting in a distortion of the crystal lattice structure. Lattice distortion can be detected by observing the size change of the diffraction peak through X-ray diffraction. Calculating the lattice distortion change rate can reflect the degree of change of the lattice distortion of the positive electrode material during the charging process.

[0058] In this text, the battery state of charge (SOC) refers to the percentage of the battery's current charge to the total battery capacity, and its value usually ranges from 0% (fully discharged) to 100% (fully charged). Specifically, the battery state of charge can be detected by the following method: using a current density of 0.25 mA / cm relative to the positive electrode 2 , charging was performed until the cut-off voltage was 4.4 V as the 100% SOC charge capacity, using 0.25 mA / cm 2 The current was discharged until the cut-off voltage reached 3.0 V, which was regarded as 0% SOC and detected.

[0059] According to the positive electrode material of the embodiment of the present application, the lattice distortion change rate meets the above conditions, indicating that the lattice distortion of the positive electrode material during the battery charging and discharging process is small, the stability of the crystal structure is good, and it can meet the use requirements under high voltage conditions, and thus has a higher energy density and a longer cycle life.

[0060] According to the embodiments of the present application, in the above formula I, a can specifically be 0.8, 0.85, 0.9, 0.95, 1.0, 1.05, 1.1, 1.15, 1.2, etc.; b can specifically be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.95, etc.; c can specifically be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.; d can specifically be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.; e can specifically be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, etc. This helps to improve the capacity and structural stability of the positive electrode material, thereby improving the energy density and cycle life of the lithium-ion battery using the positive electrode material.

[0061] According to an embodiment of the present application, in the above formula I, M includes at least one element selected from Ti, Zr, Nb, W, Al, Mg, and Sr. This helps to improve the structural stability of the positive electrode material, thereby improving the energy density and cycle life of the lithium-ion battery using the positive electrode material.

[0062] According to an embodiment of the present application, the D of the positive electrode material 50 Particle size change rate △D 50 Satisfy: 10% ≤ △D 50 ≤60%. In some specific embodiments, the D 50 Particle size change rate △D 50 Satisfy: 10% ≤ △D 50 ≤40%. As an example, the D 50 Particle size change rate △D 50 Specifically, it can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% and the like.

[0063] In this paper, △D 50 =(D 50压前 -D 50压后 ) / D 50压前 ; Among them, D 50压前 and D 50压后 are respectively D of the positive electrode material before and after being pressed 50The pressure is to apply 7.5 tons of pressure to the positive electrode material through an MCP-PD51 tester, and then use a mortar to manually grind for 20 minutes, and pass through a 300-mesh sieve to fully dissociate the positive electrode material, and take the sieve material.

[0064] Specifically, D 50 The particle size has a well-known meaning in the art, which means the particle size corresponding to when the cumulative volume distribution percentage of the positive electrode material reaches 50%, and can be measured using instruments and methods known in the art. For example, it can be measured with a laser particle size analyzer in accordance with GB / T19077-2016. The test instrument can be a Mastersizer 3000 laser particle size analyzer from Malvern Instruments Ltd., UK. 50 The D of the positive electrode material can be determined by the above method before being pressed. 50 Particle size, i.e. D 50压前 ; Then, the positive electrode material was subjected to a pressure of 7.5 tons by the MCP-PD51 tester, and then manually ground for 20 minutes using a mortar, and the positive electrode material was fully dissociated through a 300-mesh sieve, and the sieved material was taken, and the D of the sieved powder was determined by the above method. 50 Particle size, i.e. D 50压后 , and then calculated according to the above formula.

[0065] Specifically, D 50 Particle size change rate △D 50 It can reflect the bulk particle strength of the positive electrode material, △D 50 The larger the value, the weaker the strength of the positive electrode material particles. 50 Meeting the above range indicates that the positive electrode material has better particle strength, higher structural stability, and the particles are not easy to break, which is beneficial to improving the cycle life of the positive electrode material.

[0066] According to an embodiment of the present application, the specific surface area increase rate ΔSSA of the positive electrode material satisfies: 10%≤ΔSSA≤80%. In some specific embodiments, the specific surface area increase rate ΔSSA of the positive electrode material satisfies: 10%≤ΔSSA≤50%. As an example, the specific surface area increase rate ΔSSA of the positive electrode material can be 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc.

[0067] In this paper, △SSA=(SSA 压后 -SSA 压前 ) / SSA 压前 , SSA 压前 and SSA 压后They are the specific surface areas of the positive electrode material before and after being compressed; the compression is to apply a pressure of 7.5 tons to the positive electrode material through an MCP-PD51 tester, and then manually grind it with a mortar for 20 minutes, and pass it through a 300-mesh sieve to fully dissociate the positive electrode material, and take the material under the sieve.

[0068] Specifically, the specific surface area of ​​the positive electrode material has a well-known meaning in the art, specifically referring to the surface area per unit mass of the material. The specific surface area of ​​the positive electrode material can be detected by the principle of multilayer adsorption, through the amount of liquid nitrogen adsorption and desorption of the material, and by the fitting calculation method. As an example, the test can be performed using the Micro 3030 device. △SSA can be used to determine the specific surface area of ​​the positive electrode material before being compressed, that is, SSA 压前 ; Then, the positive electrode material was subjected to a pressure of 7.5 tons by the MCP-PD51 tester, and then manually ground for 20 minutes using a mortar, and passed through a 300-mesh sieve to fully dissociate the positive electrode material, and the sieved material was taken, and the specific surface area of ​​the sieved powder was determined by the above method, which is SSA 压后 , and then calculated according to the above formula.

[0069] Specifically, the specific surface area increase rate △SSA of the positive electrode material can reflect the bulk anti-powdering degree of the positive electrode material. The larger the △SSA, the easier the positive electrode material is to be powdered. If the △SSA satisfies the above range, it indicates that the positive electrode material is not easy to be powdered and has high stability, which is beneficial to improve the energy density and cycle life of the positive electrode material.

[0070] According to the embodiments of the present application, the positive electrode material can be a polycrystalline structure or a single crystal structure. In some specific embodiments, the positive electrode material is a single crystal structure. As a result, the positive electrode material can be used at a higher voltage, and has a better energy density and cycle life.

[0071] In a second aspect of the present application, a method for preparing the aforementioned positive electrode material is provided. According to an embodiment of the present application, the method comprises:

[0072] S1: The cathode material precursor, lithium salt and M-containing 1 The compounds of the elements are first mixed, and the obtained first mixture is first sintered at T1 = 850-1000° C. to obtain a first intermediate.

[0073] In this step, the cathode material precursor, lithium salt and M-containing 1 The compound of the element reacts to obtain a compound containing lithium and M 1 Oxides of elements, as first intermediates.

[0074] It is understood that the specific type of the positive electrode material precursor can be selected according to the actual situation. In some embodiments, the positive electrode material precursor can be nickel cobalt manganese hydroxide, nickel cobalt manganese oxide, nickel cobalt manganese oxyhydroxide, etc. As an example, the positive electrode material precursor can be nickel cobalt manganese hydroxide. 1 The compound of the element reacts to obtain M 1 Element nickel cobalt manganese oxide positive electrode material.

[0075] According to the embodiments of the present application, the preparation method of the positive electrode material precursor is not particularly limited. As an example, the nickel cobalt manganese hydroxide precursor can be prepared by the following steps: adding a mixed salt solution of nickel, cobalt, and manganese to a mixed alkaline solution of NaOH and NH3 in proportion, adjusting the pH value, reaction temperature, and stirring time to form a suspension, and then filtering, washing, and drying the formed suspension to obtain the positive electrode material precursor Ni b Co c Mn d (OH)2.

[0076] According to the embodiments of the present application, the type of lithium salt can also be selected according to actual needs. As an example, the lithium salt can be lithium carbonate, lithium hydroxide, lithium oxide, etc.

[0077] According to an embodiment of the present application, in the first mixing step, the lithium salt and the positive electrode material precursor can be mixed in a molar ratio of Li: (Ni+Co+Mn) (or simply lithium ratio) = 1.0~1.2:1 (specifically 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, etc.).

[0078] According to the embodiments of the present application, 1 The compound of the element can be M 1 The oxides, chlorides, nitrates, carbonates, etc. of the elements can be selected according to actual needs and are not particularly limited in this application.

[0079] According to the embodiments of the present application, 1 M in the compound of element 1 The ratio M of the amount of the element to the sum of the amount of the nickel, cobalt and manganese elements in the positive electrode material precursor 1 / (Ni+Co+Mn) satisfies 0 <M 1 / (Ni+Co+Mn)<0.1,M 1 / (Ni+Co+Mn) can be specifically 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, etc. Within the above content range, M 1The element is easy to be uniformly doped into the cathode material, for example, it can enter the lattice of the cathode material. Combined with the reaction temperature in the first sintering step, M 1 The deeper the element enters the positive electrode material, the higher the capacity can be, and the higher the voltage tolerance of the positive electrode material can be. 1 Too much element addition may block Li + The shuttling channel will result in a low capacity of the positive electrode material. 1 If the amount of element added is too low, it may not be effectively incorporated into the crystal structure, resulting in poor structural support and possible deterioration in the high voltage tolerance performance of the positive electrode material.

[0080] According to the embodiments of the present application, M 1 Including at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn. In some specific examples, M 1 The cathode material comprises at least one element selected from Ti, Zr, Nb, W, Al, Mg and Sr. This helps to improve the conductivity of the cathode material, ion diffusion, structural stability, capacity and cycle stability, and further improve the energy density and cycle life of the lithium-ion battery using the cathode material.

[0081] According to an embodiment of the present application, in this step, the positive electrode material precursor, the lithium salt and the compound containing the M1 element can be mixed evenly by a mixer. Specifically, the rotation speed R1 in the first mixing step can be 1500-2000rpm, such as 1500rpm, 1600rpm, 1700rpm, 1800rpm, 1900rpm, 2000rpm, etc. Thus, it is beneficial for the compound containing the M1 element to be evenly distributed on the surface of the positive electrode material precursor and enter the crystal structure of the first intermediate.

[0082] According to an embodiment of the present application, the first sintering temperature T1 may be 850°C, 880°C, 900°C, 920°C, 950°C, 980°C, 1000°C, etc. Within this temperature range, M 1 The elements can penetrate deeper into the positive electrode material, which can increase the high voltage tolerance performance of the positive electrode material while making the positive electrode material have a higher capacity.

[0083] According to an embodiment of the present application, the first sintering time t1 may be 15 to 25 hours, specifically 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, 24 hours, 25 hours, etc. Within the above time range, the reaction can be fully carried out without wasting too much time.

[0084] S2: The first intermediate is reacted with a 2 The compounds of the elements are second mixed, and the obtained second mixture is second sintered at 600-850° C. to obtain a second intermediate.

[0085] In this step, the first intermediate is reacted with a 2 Compound reaction of elements, M 2 The depth of the elements entering the positive electrode material is relatively shallow, mainly forming surface interface doping to obtain a second intermediate.

[0086] According to the embodiments of the present application, 2 The compound of the element can be M 2 The oxides, chlorides, nitrates, carbonates, etc. of the elements can be selected according to actual needs and are not particularly limited in this application.

[0087] According to the embodiments of the present application, 2 M in compounds of elements 2 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 2 / (Ni+Co+Mn) satisfies 0 <M 2 / (Ni+Co+Mn)<0.2,M 2 / (Ni+Co+Mn) can be specifically 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, etc. Within the above content range, combined with the reaction temperature in the second sintering step, M 2 The element enters the positive electrode material at a shallow depth, and is easy to be uniformly doped into the shallow surface layer of the positive electrode material. At the same time, it can melt and grow to effectively repair the defects on the surface of the positive electrode material, thereby increasing the cycle life of the positive electrode material. 2 Too much element addition may block Li + The shuttling channel will lead to low capacity of the positive electrode material, M 2 If the amount of elements added is too low, the defects on the surface of the positive electrode material cannot be effectively repaired, and pulverization may be accelerated during the cycle process, which is not conducive to improving the cycle life of the battery.

[0088] According to the embodiments of the present application, M 2 Including at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn. In some specific examples, M 2The cathode material comprises at least one element selected from Ti, Zr, Nb, W, Al, Mg and Sr. This helps to improve the conductivity of the cathode material, ion diffusion, structural stability, capacity and cycle stability, and further improve the energy density and cycle life of the lithium-ion battery using the cathode material.

[0089] According to an embodiment of the present application, in this step, the first intermediate and the compound containing the M2 element can be mixed evenly by a mixer. Specifically, the rotation speed R2 in the second mixing step can be 1800-2300 rpm, such as 1800 rpm, 1900 rpm, 2000 rpm, 2100 rpm, 2200 rpm, 2300 rpm, etc. Thus, the compound containing the M2 element is evenly distributed on the surface of the first intermediate and enters the shallow surface layer of the positive electrode material.

[0090] According to the embodiment of the present application, the rotation speed R2 in the second mixing step and the rotation speed R1 in the first mixing step can satisfy R2-R1=300-800, specifically 300, 400, 500, 600, 700, 800, etc. Meeting the above rotation speed requirements, the additives can be dispersed to a certain extent in the first mixing step, and combined with the higher sintering temperature, the additives are more easily evenly diffused into the material body, and in the second mixing step, the above rotation speed can make the additives evenly distributed, which is conducive to the reaction with the material surface interface, can improve the stability of the material surface, resist the electrolyte side reaction, and improve the cycle performance; with the above rotation speed difference, the additives in different mixing steps can give full play to the role of bulk doping and surface doping, which is more conducive to improving the performance of the positive electrode material.

[0091] According to the embodiment of the present application, the temperature T2 of the second sintering can be 600°C, 650°C, 700°C, 750°C, 800°C, etc. Within this temperature range, the M 2 The compound of the element can be melted to repair the defects on the surface of the first intermediate and form a smooth surface morphology. 2 The depth to which the elements can enter the positive electrode material is shallow, making the positive electrode material have a higher capacity.

[0092] According to the embodiment of the present application, the second sintering time t2 can be 12 to 18 hours, specifically 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, etc. Within the above time range, the reaction can be fully carried out without wasting too much time.

[0093] S3: The second intermediate and the M-containing 3 The compounds of the elements are thirdly mixed, and the obtained third mixture is thirdly sintered at 450-650° C. to obtain the positive electrode material.

[0094] In this step, the second intermediate is reacted with the M-containing 3 Compound reaction of elements, M 3 The elements are mainly coated on the surface of the second intermediate to obtain the positive electrode material.

[0095] According to the embodiments of the present application, 3 The compound of the element can be M 3 The oxides, chlorides, nitrates, carbonates, etc. of the elements can be selected according to actual needs and are not particularly limited in this application.

[0096] According to the embodiments of the present application, 3 M in the compound of element 3 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 3 / (Ni+Co+Mn) satisfies 0 <M 3 / (Ni+Co+Mn)<0.1,M 3 / (Ni+Co+Mn) can be specifically 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, etc. Within the above content range, combined with the reaction temperature in the third sintering step, M 3 The elements are mainly coated on the surface of the positive electrode material, which can reduce the side reactions during the cycle and further reduce the gas generation of the positive electrode material during the cycle. 3 If the amount of added elements is too high, most of them will remain on the surface due to the low temperature of the third sintering, which may increase the impedance of the positive electrode material. 3 If the amount of elements added is too low, the positive electrode material cannot be effectively covered, which may cause direct contact between the positive electrode material and the electrolyte, increase side reactions, and produce excessive gas after long-term circulation, leading to safety risks.

[0097] According to the embodiments of the present application, M 3 Including at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn. In some specific examples, M 3 The cathode material comprises at least one element selected from Ti, Zr, Nb, W, Al, Mg and Sr. This helps to improve the conductivity of the cathode material, ion diffusion, structural stability, capacity and cycle stability, and further improve the energy density and cycle life of the lithium-ion battery using the cathode material.

[0098] According to an embodiment of the present application, in this step, the second intermediate and the M-containing 3Specifically, the rotation speed R3 in the third mixing step can be 1000-1600 rpm, such as 1000 rpm, 1100 rpm, 1200 rpm, 1300 rpm, 1400 rpm, 1500 rpm, 1600 rpm, etc. Thus, it is beneficial to 3 The compound of the element is evenly distributed on the surface of the first intermediate and enters into the crystal structure of the positive electrode material.

[0099] According to an embodiment of the present application, the rotation speed R3 in the third mixing step and the rotation speed R2 in the second mixing step may satisfy R2-R3=800-1300, such as 800, 900, 1000, 1100, 1200, 1300, etc.

[0100] According to an embodiment of the present application, the rotation speed R3 in the third mixing step and the rotation speed R1 in the first mixing step may satisfy R1-R3=200-800, specifically 200, 300, 400, 500, 600, 700, 800, etc.

[0101] To meet the above speed requirements, the first mixing is at an intermediate speed, mainly because the sintering temperature is the highest, and the additives are easier to diffuse evenly into the material body. If the speed is too high, the additive dispersion reaction will be too strong, which will affect the amount of Li embedded and the capacity will be low, so the speed does not need to be the highest; the second mixing speed is the highest, mainly because the subsequent sintering temperature is in the middle section, and at the same time, it is hoped that the additives are the effect of surface interface doping, so the high speed is used to make the additives evenly distributed, which is conducive to the reaction with the material surface interface, which can improve the stability of the material surface, resist the electrolyte side reaction, and improve the cycle performance; the third mixing speed is the lowest, because the reaction temperature of the subsequent sintering is low, and the additives are in a surface attachment state. If the additives are evenly distributed, it will affect the material ions entering the electrolyte, increase the impedance, and reduce the capacity, so it is necessary to achieve the effect of island distribution of additives, so the speed is the lowest. The speed difference at different stages can make the corresponding additives play the effects of bulk doping, surface doping and avoiding coating, and further improve the performance of the positive electrode material.

[0102] According to an embodiment of the present application, the temperature T3 of the third sintering may be 450°C, 500°C, 550°C, 600°C, 650°C, etc. Within this temperature range, M 3 The elements are mainly covered on the surface of the positive electrode material, which can effectively reduce the side reactions between the positive electrode material and the electrolyte, thereby reducing gas production, extending the cycle life of the battery and improving the safety of the battery.

[0103] According to the embodiment of the present application, the third sintering time t3 can be 7 to 13 hours, specifically 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, etc. Within the above time range, the reaction can be fully carried out without wasting too much time.

[0104] According to the embodiment of the present application, in the above three sintering steps, the M 2 The amount of the compound containing M is greater than that of the compound containing M 1 The amount of the compound containing M 2 The amount of the compound containing M is greater than that of the compound containing M 3 Thus, M with a suitable amount of 1 Elements enter the crystal structure of the positive electrode material and will not be enriched at the grain boundary or surface. 2 Elements entering the shallow surface layer of the positive electrode material can effectively increase the capacity of the positive electrode material. 3 The elements can effectively cover the surface of the positive electrode material without affecting the conductivity of the positive electrode material.

[0105] In this method, doping and coating elements are introduced by three sintering processes. 1 、M 2 and M 3 By reacting with the positive electrode material at different temperatures, M 1 、M 2 and M 3 The positive electrode materials that have entered different reaction depths, and the doped elements and positive electrode materials have achieved different degrees of fusion effects, also repair the positive electrode materials. As a result, the obtained positive electrode materials can maintain good crystal structure stability under high voltage conditions, thereby improving the cycle life of the battery using the positive electrode materials.

[0106] In a third aspect of the present application, a lithium-ion battery is provided. According to an embodiment of the present application, the lithium-ion battery comprises the positive electrode material described above or the positive electrode material prepared by the method described above. The lithium-ion battery has a high energy density and a long cycle life.

[0107] It can be understood that there is no particular limitation on the specific type of the lithium-ion battery, which can be a primary battery or a secondary battery; the shape of the lithium-ion battery can be a cylindrical battery, a square battery, or a battery of any other shape, etc., and according to the outer packaging classification, the lithium-ion battery can be a hard shell battery, a soft pack battery, etc.

[0108] Typically, a lithium-ion battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by winding or lamination process, and the electrode assembly and the electrolyte can be contained in an outer package. During the charge and discharge process of the lithium-ion battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, which mainly plays the role of preventing the positive and negative electrodes from short-circuiting, and at the same time allows ions to pass through.

[0109] In some embodiments, the positive electrode sheet may include a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, the positive electrode active material layer includes a positive electrode active material, a conductive agent and a binder, and the positive electrode current collector may include a metal foil, for example, the metal foil may be an aluminum foil. The positive electrode active material may include the positive electrode material of the first aspect of the present application or the positive electrode material prepared by the method described in the second aspect of the present application. The conductive agent may include acetylene black, single-walled carbon nanotubes and conventional materials in the art. The binder may be polyvinylidene fluoride (PVDF) and conventional materials in the art.

[0110] In some embodiments, the negative electrode sheet may include a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, the negative electrode active material layer may include a negative electrode active material, a thickener, a conductive agent and a binder, wherein the negative electrode current collector may be a metal foil, for example, the metal foil may be a copper foil. The negative electrode active material may include artificial graphite, natural graphite, a silicon-containing carbon-based composite material, a lithium-containing metal composite material, a lithium metal material and a common negative electrode active material in the art. The thickener may be a thickener sodium carboxymethyl cellulose (CMC-Na) and a conventional material in the art. The conductive agent may be acetylene black and a conventional material in the art. The binder may be styrene-butadiene rubber and a conventional material in the art.

[0111] In some embodiments, the separator can be a separator known in the art that can be used in lithium-ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, and the like.

[0112] The fourth aspect of the present application provides an electrical device, comprising the lithium-ion battery described in the third aspect of the present application. The electrical device has all the features and advantages of the lithium-ion battery described above, which will not be described one by one here.

[0113] In some embodiments, the electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited to these.

[0114] The embodiments of the present application are described in detail below.

[0115] Example 1

[0116] (1) Nickel sulfate, cobalt sulfate and manganese sulfate are dissolved in a molar ratio of 60:20:20 among nickel, cobalt and manganese elements to obtain a mixed salt solution with a concentration of 2 mol / L; sodium hydroxide is dissolved into a precipitant solution with a concentration of 7 mol / L; ammonia water is dissolved into a complexing agent solution with a concentration of 6 mol / L. 100 L of the mixed salt solution, the precipitant solution and the complexing agent solution are introduced into a reactor in parallel, and mixed for 20 hours at a temperature of 55°C, a pH value of 9.5 and a stirring speed of 600 rpm. Then, under the protection of a nitrogen atmosphere, the precursor slurry is filtered and washed, and the filter cake is dried at 120°C and sieved to obtain a nickel-cobalt-manganese hydroxide precursor.

[0117] (2) The precursor, LiOH and TiO2 were heated from room temperature to 950°C in an oxygen atmosphere according to a molar ratio of Li / (Ni+Co+Mn) / Ti=1.10:1.00:0.01, and kept at this temperature for 18 hours for high temperature reaction. After cooling, crushing and screening, the first intermediate Li 1.1 Ni 0.594 Co 0.198 Mn 0.198 Ti 0.010 O2.

[0118] (3) The first intermediate and TiO2 were heated from room temperature to 700°C in an air atmosphere according to a molar ratio of (Ni+Co+Mn) / Ti=1.0:0.02, kept at this temperature for 5 hours, and cooled naturally to obtain the second intermediate Li 1.1 Ni 0.583 Co 0.194 Mn 0.194 Ti 0.029 O2.

[0119] (4) The second intermediate and TiO2 were heated from room temperature to 500°C in an air atmosphere at a molar ratio of (Ni+Co+Mn) / Ti=1.0:0.01, kept at this temperature for 5 hours, and cooled naturally to obtain the positive electrode material Li 1.1 Ni 0.577 Co 0.192 Mn 0.193 Ti0.039 O2.

[0120] (5) Preparation of positive electrode: The prepared positive electrode material, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 93:5:2, and mixed with an appropriate amount of solvent N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The obtained positive electrode slurry was coated on an aluminum foil (thickness: 20 μm) as a collector, dried at 120°C for 5 minutes, and then compressed using a roller press to prepare a positive electrode active material layer with a single-sided coating amount of 20 mg / cm 2 The positive electrode.

[0121] (6) Preparation of button cell: In a glove box under an argon atmosphere, the positive electrode obtained above was punched into a disc shape with a diameter of 14 mm to make a positive electrode for a button cell. As the negative electrode, a material obtained by punching metallic lithium into a disc shape with a diameter of 15 mm was used. In addition, as an electrolyte, a solution obtained by dissolving 1.0M LiPF6 in a mixed solvent of ethylene carbonate (EC) and dimethyl carbonate (DMC) (volume ratio 1:1) was prepared. The positive electrode and the negative electrode were stacked with a separator (material: polypropylene, thickness: 23 μm), placed in a button cell container, the electrolyte was injected, and the upper cover was covered to obtain a button cell.

[0122] Embodiments 2 to 26

[0123] Same as Example 1, specific differences are shown in Table 1.

[0124] Comparative Examples 1 to 7

[0125] Same as Example 1, specific differences are shown in Table 1.

[0126] Performance testing:

[0127] 1. Lattice distortion rate test: Before the positive electrode material is assembled into the battery, the J0 of the positive electrode material is obtained by X-ray diffractometer test; after the positive electrode material is assembled into the battery, the two batteries are charged to 50% SOC and 100% SOC respectively, the batteries are disassembled, the positive electrode material on the positive electrode sheet is scraped off, and the J0 of the positive electrode material is tested by X-ray diffractometer under the same test conditions. 50 , J 100 The specific test conditions are to lay the sample flat on the test glass dish, use SmartLab9kW to perform XRD10-80° scanning at a scanning speed of 1° / min to obtain full spectrum data, use SmartLab StudioⅡ software for refinement processing, and calculate the lattice distortion rate.

[0128] 2. D 50Particle size test: using Malvern 3000 instrument, after the blank background test is completed, add the sample to the sample pool, make the sample shading reach 10%-20%, start ultrasound to disperse the sample, after ultrasound is completed for 30s, click sample measurement to perform particle size distribution test. Specifically. The test sample includes the positive electrode material directly obtained from the preparation (i.e. before pressing) and the positive electrode material obtained by applying 7.5 tons of pressure to the positive electrode material through the MCP-PD51 tester, and then manually grinding it with a mortar for 20 minutes and passing it through a 300-mesh sieve (i.e. after pressing), and then according to △D 50 =(D 50压前 -D 50压后 ) / D 50压前 Calculate D 50 Particle size change rate △D 50 The SEM photos of the positive electrode material obtained in Example 1 before and after pressing are shown in Figure 2 and Figure 3 The SEM photos of the positive electrode material obtained in Comparative Example 1 before and after pressing are shown in Figure 4 and Figure 5 .

[0129] 3. Specific surface area test: Use the Mack 3030 equipment to test, weigh 4g of sample and add it to the sample tube, degas the sample at 300℃*1h in the degassing station, and test the specific surface area of ​​the treated sample in a low-temperature liquid nitrogen environment. Specifically. The test sample includes the positive electrode material directly obtained from the preparation (i.e. before pressing) and the positive electrode material obtained by applying 7.5 tons of pressure to the positive electrode material through the MCP-PD51 tester, and then manually grinding it in a mortar for 20 minutes and passing it through a 300-mesh sieve (i.e. after pressing), and then according to △SSA=(SSA 压后 -SSA 压前 ) / SSA 压前 Calculate the specific surface area increase rate △SSA.

[0130] 4. Capacity and cycle retention test: Place the button battery unit for 24 hours. After the open circuit voltage (OCV) stabilizes, make the current density relative to the positive electrode 0.25mA / cm 2 The initial charge capacity was taken as the charge capacity until the cut-off voltage was 4.4 V, and the initial discharge capacity was taken as the capacity when the cut-off voltage was 3.0 V after resting for 0.2 hours. Then the current density relative to the positive electrode was set to 2.5 mA / cm 2 The battery was charged and discharged 80 times in a cycle, and the capacity retention rate after 80 cycles was calculated and evaluated as the cycle durability.

[0131] Table 1: Process parameters of the preparation process

[0132]

[0133]

[0134] Table 2 Performance parameters of positive electrode materials

[0135]

[0136]

[0137] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0138] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0139] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode material, characterized in that: Including compounds shown in formula I: Li a Ni b Co c Mn d M e O2 of formula I In formula I, 0.8≤a≤1.2, 0<b<1, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.4; M includes at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn; The lattice distortion change rate of the positive electrode material is 1%≤△J 50 ≤20%, 2%≤△J 100 ≤40%; where △J 50 =(J 50 -J0) / J0,△J 100 =(J 100 -J0) / J0, J0, J 50 , J 100 The lattice distortion of the positive electrode material when the charging states of the battery using the positive electrode material are 0% SOC, 50% SOC and 100% SOC respectively.

2. The positive electrode material according to claim 1, characterized in that 1%≤△J 50 ≤10%,2%≤△J 100 ≤20%。 3. The positive electrode material according to claim 1, characterized in that M includes at least one element of Ti, Zr, Nb, W, Al, Mg, and Sr.

4. The positive electrode material according to claim 1, characterized in that The positive electrode material D 50 Particle size change rate △D 50 Satisfy: 10% ≤ △D 50 ≤60%, preferably 10%≤△D 50 ≤40%; Among them, △D 50 =(D 50压前 -D 50压后 ) / D 50压前 ; D 50压前 and D 50压后 are respectively D of the positive electrode material before and after being pressed 50 The pressure is to apply 7.5 tons of pressure to the positive electrode material through an MCP-PD51 tester, and then grind it manually for 20 minutes using a mortar, and pass it through a 300-mesh sieve to take the material under the sieve.

5. The positive electrode material according to claim 1, characterized in that The specific surface area increase rate ΔSSA% of the positive electrode material satisfies: 10%≤ΔSSA%≤80%, preferably 10%≤ΔSSA%≤50%; Where, ΔSSA%=(SSA 压后 -SSA 压前 ) / SSA 压前 ; SSA 压前 and SSA 压后 They are the specific surface areas of the positive electrode material before and after being compressed; the compression is to apply a pressure of 7.5 tons to the positive electrode material through an MCP-PD51 tester, and then manually grind it with a mortar for 20 minutes, and pass it through a 300-mesh sieve to take the material under the sieve.

6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: include: The cathode material precursor, lithium salt and M-containing 1 The compounds of the elements are first mixed, and the obtained first mixture is first sintered at T1=850°C to 1000°C to obtain a first intermediate; The first intermediate is mixed with a 2 The compounds of the elements are mixed for the second time, and the obtained second mixture is sintered for the second time at T2 = 600° C. to 850° C. to obtain a second intermediate; The second intermediate and the 3 The compounds of the elements are mixed for the third time, and the obtained third mixture is sintered for the third time at T3 = 450° C. to 650° C. to obtain the positive electrode material; Among them, M 1 、M 2 、M 3 Each independently includes at least one element selected from Ti, Zr, Nb, W, P, Al, Mg, V, Ca, Sr, Cr, Fe, B, Ga, In, Si, Mo, Y, Sn, V, Cu, Ag, and Zn.

7. The method according to claim 6, characterized in that The M-containing 2 The amount of the compound containing M is greater than that of the compound containing M 1 the amount of the compound of the element; and / or The M-containing 2 The amount of the compound containing M is greater than that of the compound containing M 3 The amount of the compound of the element.

8. The method according to claim 7, characterized in that Satisfy at least one of the following conditions: The M-containing 1 M in the compound of element 1 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 1 / (Ni+Co+Mn) satisfies 0 <M 1 / (Ni+Co+Mn)<0.1; The M-containing 2 M in the compound of element 2 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 2 / (Ni+Co+Mn) satisfies 0 <M 2 / (Ni+Co+Mn)<0.2; The M-containing 3 M in the compound of element 3 The ratio M of the amount of the substance of the element to the sum of the amounts of the nickel, cobalt and manganese elements in the positive electrode material precursor 3 / (Ni+Co+Mn) satisfies 0 <M 3 / (Ni+Co+Mn)<0.

1.

9. The method according to claim 7, characterized in that: At least one of the following conditions is met: the rotation speed R1 of the first mixing is 1500-2000 rpm; The first sintering time t1 is 15 to 25 hours; The second mixing speed R2 is 1800-2300 rpm; The second sintering time t2 is 12 to 18 hours; The rotation speed R3 of the third mixing is 1000-1600 rpm; The third sintering time t3 is 7 to 13 hours.

10. The method according to claim 9, characterized in that Satisfy at least one of the following conditions: R2-R1=300-800; R2-R3=800~1300; R1-R3=200~800.

11. The method according to claim 6, characterized in that M 1 、M 2 、M 3 Each independently includes at least one element among Ti, Zr, Nb, W, Al, Mg and Sr.

12. A lithium ion battery, characterized in that: The positive electrode material comprises the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the method according to any one of claims 6 to 11.

13. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 12.